Pentagon Fraud Analysis in Detecting Potential Financial Statement Fraud of Banking Companies in Indonesia - Hidayah, Erna; Saptarini, Galih Devi (Proceeding UII-ICABE, 2020)
This study aims to determine the potential for financial statement fraud by using pentagon fraud analysis. Pentagon fraud is a concept that explains the factors that cause someone to commit fraud, namely pressure, opportunity, rationalization, capability, and arrogance. In this study, the pressure factor is proxy by using financial targets and external pressure. The opportunity factor is proxied by using the nature of industry and effective monitoring. The rationalization factor is proxied by using a change in auditor. The capability factor is proxied by using change in directors. Finally, the arrogance factor is proxied by using the frequent number of CEO’s picture. This study uses the F-Score Model to see the potential for fraudulent financial statements. The sample in this study were 33 banking companies listed on the Indonesia Stock Exchange in 2013-2017 that met certain criteria. The analysis technique used is panel data regression analysis and hypothesis testing using the t test. The results of this study indicate that the financial target and change in directors variables are proven to have a significant positive effect in detecting the potential for financial statement fraud, but the external pressure and nature of industry variables have a negative effect in detecting the potential for financial statement fraud. While the effective monitoring variable; change in auditor, and frequent number of CEO’s picture has no effect in detecting potential fraudulent financial statements. Keywords: fraud pentagon, f-sore, potential fraudulent financial statements